ANALISIS KEDUDUKAN ANAK HASIL PERKAWINAN SIRRI DALAM PEMBAGIAN WARIS PERSPEKTIF HUKUM ISLAM DI PENGADILAN AGAMA SORONG - Izza, Nurull; Hujriman (Prodi Hukum Keluarga (Akhwal Syahsiyyah) IAIN Sorong, 2024)
This research discusses the analysis of the position of children resulting from unregistered marriages in the division of inheritance from an Islamic legal perspective at the Sorong Religious Court. The aim of this research is to analyze the position of children resulting from unregistered marriages and analyze the form of determining inheritance for children resulting from unregistered marriages from an Islamic legal perspective at the Sorong Religious Court. This type of research is field research. Data collection methods through literature studies and interviews. Data analysis takes the form of qualitative descriptive analysis through a process of data reduction, data presentation, and conclusions or verification. The results of this research are: 1. The position of children resulting from unregistered marriages only has a civil relationship with the mother and her mother's family. However, children resulting from unregistered marriages can have a civil relationship with their father if it can be proven. 2. For children resulting from an unregistered marriage to receive inheritance from their parents, their parents' marriage must first be ratified. Once proven, the child can receive his share of inheritance as legitimate children in general.